Visualization of Tunable Weyl Line in A–A Stacking Kagome Magnets. Issue 3 (15th December 2022) - Cheng, Zi‐Jia; Belopolski, Ilya; Tien, Hung‐Ju; Cochran, Tyler A.; Yang, Xian P.; Ma, Wenlong; Yin, Jia‐Xin; Chen, Dong; Zhang, Junyi; Jozwiak, Chris; Bostwick, Aaron; Rotenberg, Eli; et al.
Abstract: Kagome magnets provide a fascinating platform for a plethora of topological quantum phenomena, in which the delicate interplay between frustrated crystal structure, magnetization, and spin–orbit coupling (SOC) can engender highly tunable topological states. Here, utilizing angle‐resolved photoemission spectroscopy, the Weyl lines are directly visualized with strong out‐of‐plane dispersion in the A–A stacked kagome magnet GdMn6 Sn6 . Remarkably, the Weyl lines exhibit a strong magnetization‐direction‐tunable SOC gap and binding energy tunability after substituting Gd with Tb and Li, respectively. These results not only illustrate the magnetization direction and valence counting as efficient tuning knobs for realizing and controlling distinct 3D topological phases, but also demonstrate AMn6 Sn6 (A = rare earth, or Li, Mg, or Ca) as a versatile material family for exploring diverse emergent topological quantum responses. Abstract : This work provides the spectroscopic evidence of 3D Weyl lines in Mn‐based kagome magnets with the systematic angle‐resolved photoemission spectroscopy (ARPES) experiment. Interestingly, the bandgap and binding energies of the Weyl lines can be tuned through cation engineering, which demonstrate the system as a promising platform for realizing controllable and robust 3D quantum devices.